In Vitro Incorporation and Metabolism of Icosapentaenoic and Docosahexaenoic Acids in Human Platelets - Effect on Aggregation - Croset, Martine; Lagarde, M (Thrombosis and Haemostasis, 1986)
Washed human platelets were pre-loaded with icosapentaenoic acid (EPA), docosahexaenoic acid (DHA) or EPA + DHA and tested for their aggregation response in comparison with control platelets. In fatty acid-rich platelets, an inhibition of the aggregation could be observed when induced by thrombin, collagen or U-46619. The strongest inhibition was observed with DHA-rich platelets and it was reduced when DHA was incorporated in the presence of EPA.Study of fatty acid distribution in cell lipids after loading showed that around 90% of EPA or DHA taken up was acylated into phospholipids and a very small amount (less than 2%) remained in their free and hydroxylated forms. DHA was more efficiently acylated into phosphatidylethanolamine (PE) than into phosphatidylinositol (PI) in contrast to what observed with EPA, and both acids were preferentially incorporated into phosphatidylcholine (PC). EPA inhibited total incorporation of DHA and increased its relative acylation into PE at the expense of PC. In contrast, DHA did not affect the acylation of EPA. Upon stimulation with, thrombin, EPA was liberated from phospholipids and oxygenated (as judged by the formation of its monohydroxy derivative) whereas DHA was much less metabolized, although consistently transferred into PE.It is concluded that EPA and DHA might affect platelet aggregation via different mechanisms when pre-loaded in phospholipids. Whereas EPA is known to alter thromboxane A2 metabolism from endogenous arachidonic acid, by competing with it, DHA might act directly at the membrane level for inhibiting aggregation.
Keywords: Platelets; Aggregation; Icosapentaenoic and docosahexa-enoic acids; Phospholipids